Gadd45a deletion aggravates hematopoietic stem cell dysfunction in ATM-deficient mice - Chen, Yulin; Yang, Runan; Guo, Peng; Ju, Zhenyu (Protein & cell, 2014)
Ataxia telangiectasia mutated （ATM） kinase plays an essential role in the maintenance of genomic stability. ATM-deficient （ATM-/-） mice exhibit hematopoietic stem cell （HSC） dysfunction and a high incidence of lym- phoma. Gadd45a controls cell cycle arrest, apoptosis and DNA repair, and is involved in the ATM-p53 mediated DNA damage response. However, the role of Gadd45a in regulating the functionality of ATM-/- HSCs is unknown. Here we report that Gadd45a deletion did not rescue the defects of T-cells and B-cells development in ATM-/- mice. Instead, ATM and Gadd45a double knockout （ATM-/- Gadd45a-/-） HSCs exhibited an aggravated defect in long-term self-renewal capacity compared to ATM-/- HSCs in HSC transplantation experiments. Fur- ther experiments revealed that the aggravated defect of ATM-/- Gadd45a-/- HSCs was due to a reduction of cell proliferation, associated with an accumulation of DNA damage and subsequent activation of DNA damage response including an up-regulation of p53-p21 signal- ing pathway. Additionally, ATM-/- Gadd45a-/- mice showed an increased incidence of hematopoietic malignancies, as well as an increased rate of metastasis than ATM-/- mice. In conclusion, Gadd45a deletion aggravated the DNA damage accumulation, which sub- sequently resulted in a further impaired self-renewal capacity and an increased malignant transformation in ATM-/- HSCs.